The role of gender and age in the perception of a menopausal woman - Bielawska-Batorowicz, Eleonora; Cwalina, Ewa; Cieślik, Izabela (Menopause Review/Przegląd Menopauzalny, 2003)
Objectives: The aim of the study was to look at non-medical aspects of menopause: 1) the concept of menopause and social perception of menopausal women, 2) the role of gender and age in creating an image of a menopausal woman. Design: Cross-sectional study with random sample; qualitative and quantitative analysis of data collected through questionnaire. Material and methods: The random sample consisted of 320 subjects (160 men and 160 women) aged 23–66 evenly distributed in 4 age groups. To describe a menopausal woman they completed the adjective checklist and answered open questions related to menopausal features and associations with the word ‘‘menopause”. Factor analysis of checklist data revealed 7 factors (emotions, behaviour, physical condition, activity, isolation, dominance in social relationships, self-confidence) that explained 58% of variance. Results: According to ANOVA younger persons created more negative image of a menopausal woman, males shared more negative views than females. Further analyses indicated that the majority of the sample created the image with both negative and positive elements, however negative aspects were indicated more often. The content of associations with the word ‘‘menopause” was related to gender, but the general tone of these associations was similarly negative. Conclusions: The sample shared stereotypical and mostly negative image of a menopausal woman. This tendency was strongly related to younger age and male gender.